Protivirusne učinkovine proti SARS-CoV-2 za zdravljenje bolezni covid-19 - Tomašič, Tihomir (Farmacevtski vestnik, 2020)
The covid-19 disease, which is caused by SARSCoV-2, can be fatal. Therefore, there is an urgent need for the development of novel antiviral drugs against SARS-CoV-2. In this review article, we describe macromolecular structures of SARS-CoV-2 as potential targets for antiviral drugs. Furthermore, we present drugs or drug candidates with antiviral mode of action and promising effects in covid-19 therapy.
Keywords: covid-19; koronavirus; Pandemije; protivirusne učinkovine; SARS-CoV-2; Virusne infekcije